2018
DOI: 10.1038/s41598-018-32315-3
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic detection of mesothelioma by circulating calretinin and mesothelin – a case-control comparison nested into a prospective cohort of asbestos-exposed workers

Abstract: Malignant mesothelioma (MM) is strongly associated with a previous asbestos exposure. To improve timely detection of MM in asbestos workers, better screening tools – like minimally-invasive biomarkers – are desirable. Between 2008 and 2018 2,769 patients with benign asbestos-related diseases were recruited to participate in annual screens. Using a nested case-control design the protein markers calretinin and mesothelin were determined by enzyme-linked immunosorbent assays in prediagnostic plasma samples of 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 54 publications
3
61
0
2
Order By: Relevance
“…Such an early detection approach has already been published for mesothelioma, reporting that sCRT (in combination with serum mesothelin) enabled prediagnostic detection of mesothelioma with an AUC of 0.74. 19 The biology and origin of CRT release into the bloodstream remains an open question. Since immunohistochemical studies on serous ovarian cancer reported variable CRT positivity in 0-40%, 15 it is possible that CRT promotes growth and survival of ovarian cancer cells, as it has been shown in vitro for mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such an early detection approach has already been published for mesothelioma, reporting that sCRT (in combination with serum mesothelin) enabled prediagnostic detection of mesothelioma with an AUC of 0.74. 19 The biology and origin of CRT release into the bloodstream remains an open question. Since immunohistochemical studies on serous ovarian cancer reported variable CRT positivity in 0-40%, 15 it is possible that CRT promotes growth and survival of ovarian cancer cells, as it has been shown in vitro for mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of sCRT were determined as described by Johnen et al ., using the commercially available Calretinin enzyme‐linked immunoabsorbent assay kit by DLD Diagnostika GmbH . The assay is based on polyclonal antibodies developed by Raiko et al .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations